2021
DOI: 10.33151/ajp.18.820
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Purposeful Teaching, Learning and Assessment of Crisis Resource Management Principles and Practices in the Undergraduate Pre-Hospital Emergency Care Curriculum: A Narrative Literature Review

Abstract: IntroductionTraditionally, undergraduate emergency medical care (EMC) training programs have, over the years, typically focussed on developing individuals with proficiency in clinical skills who can perform complex procedures in the act of administering safe and effective emergency care in the pre-hospital setting. A shortcoming of this training relates to the attention given to the soft skills needed to work efficiently in a team-based environment. Crisis resource management (CRM) is a structured, evidence-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“… 40 , 41 These findings suggest that, while some PECP can attain and maintain patient and crew safety consequent of their knowledge of CRM, others may have poor compliance to patient safety due to their lack of familiarity with and poor knowledge of the principles and practice of CRM. This conclusion highlights the need for purposeful teaching, learning and assessment of CRM principles and practices in the undergraduate pre-hospital emergency care curriculum, as proposed by Rowland et al 13 However, it is worth noting that improving patient safety in the pre-hospital setting requires a multifaceted approach. Training must be accompanied by improvements to clinical systems, and maintenance of a true culture of safety in the workplace.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“… 40 , 41 These findings suggest that, while some PECP can attain and maintain patient and crew safety consequent of their knowledge of CRM, others may have poor compliance to patient safety due to their lack of familiarity with and poor knowledge of the principles and practice of CRM. This conclusion highlights the need for purposeful teaching, learning and assessment of CRM principles and practices in the undergraduate pre-hospital emergency care curriculum, as proposed by Rowland et al 13 However, it is worth noting that improving patient safety in the pre-hospital setting requires a multifaceted approach. Training must be accompanied by improvements to clinical systems, and maintenance of a true culture of safety in the workplace.…”
Section: Discussionmentioning
confidence: 75%
“… 12 It has been suggested that CRM can reduce the incidence of clinical error and contribute to effective teamwork and the success of a pre-hospital emergency care plan when applied in combination with good clinical practice. 13 Rall et al report that an emergency care practitioner’s knowledge of and adherence to the principles of CRM can enhance patient safety during pre-hospital care. 4 Despite these benefits, very few undergraduate pre-hospital EMC training programs purposefully teach and assess CRM principles and skills in their curricula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, ECPs who participated in this study recognised ‘poor leadership and management practices’ as factors that could contribute to errors during pre-hospital emergency care. The hierarchical parameters entrenched by the level of qualification and training in the pre-hospital environment ensures that the followership role is often assigned to lower-level cadres, while practitioners with higher qualifications assume leadership roles (Rowland, Adefuye & Vincent-Lambert 2021 ). This practice can lead to intimidation by and unsolicited pressure from colleagues, which can be a source of errors during pre-hospital emergency care, as indicated by the participants of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, participants of our study reported that ‘ineffective teamwork’ could influence patient safety in the pre-hospital emergency care setting. It is recommended that deliberate teaching and training on principles and practice of crisis resource management is undertaken to enhance teamwork skills of health care practitioners (Rowland et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%